O duplo em Saramago - Dworzak, Regina Helena (2006)
The objective of this work is to study the myth of the double as character in the novel The Double, of Jose Saramago, published in 2002. To explain the form of this myth in the Contemporarity we cover the trajectory of the myth since the sprouting of the reason and the conscience of itself in the beginning of the man. As hypothesis, we understand the myth of the double as non-separable part of the nature human being who will follow the evolution of the artistic phenomena, since the first representations in the walls of the caves until the fragmentary art contemporary, being its literary construction impregnated by the historical and social-cultural modifications, transforming the literary language into instrument of critical and metalanguage. To justify the study of the myth to be the primordial form of narration, oral in principle, suffering to a mutation to be registered for the writing, losing the sacred character and acquiring literary contours. It is in this aspect that we observe the transformation of the myth, more specifically, from the work of Edgar Allan Poe, the short story William Wilson, chosen for its importance in the formatting of a double modern, fruit of a society that entries for the Modern Age for the Industrial Revolution and its consequences, such as the growth of the cities and the massification of the population; until the romance The Double, presenting a double in search of an identity that if presents unstable. Analyzing the double while character, we verify the influences of the historical and social-cultural factors in its composition, beyond its relation with the author and the narrator of the literary text, the some voices that if face in the narrative and propitiate to look at intent disclosing the double that if it projects in these relations and it constructs a multifaceted text